GENERAL DESCRIPTION OF PLANT REPRODUCTION - Abdunazarova Gavhar Asliddin qizi; Hayitova Nargiza (Galaxy International Interdisciplinary Research Journal, 2023)
Plant reproduction has the characteristics of all living organisms in plants. Plants also breathe, eat, grow, reproduce and eventually die. The creation of new individuals similar to themselves by all living organisms is called reproduction. In the plant world, there are different types of reproduction. Terrestrial as well as higher plants reproduce in three ways (sexual, asexual and vegetative).